Comparative evaluation of chloroplast DNA barcoding markers for authenticating ethnomedicinal plants from Surigao del Sur, Philippines - FREDDIE A. BLASCO; RUBY RATERTA; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2025)
Abstract. Blasco FA, Raterta R, Alejandro GJD. 2025. Comparative evaluation of chloroplast DNA barcoding markers for authenticating ethnomedicinal plants from Surigao del Sur, Philippines. Biodiversitas 26: 5195-5203. Traditional medicine utilizing ethnomedicinal plants remains crucial for healthcare in developing countries, with authentication being critical for safety and efficacy. DNA barcoding offers a molecular solution for accurate species identification, particularly important for poorly documented flora in biodiversity hotspots. This study evaluated the performance of four chloroplast DNA barcoding regions (rbcL, matK, trnL-F, and trnH-psbA) for authenticating ethnomedicinal plants from the biodiverse Surigao del Sur mountain range, Philippines. This represents the first comprehensive molecular reference dataset for Surigao del Sur ethnomedicinal flora. Fresh leaf samples from 50 ethnomedicinal plant species representing 43 genera and 31 families were collected from three municipalities (Lanuza, Tago, and Tandag). Barcode performance of the four markers was assessed based on PCR success, sequencing quality, BLAST identification accuracy, genetic distance analysis, and phylogenetic reconstruction. The trnH-psbA region achieved the highest PCR amplification success (100%), while trnL-F exhibited optimal balanced performance with 94% PCR success rate. BLAST analysis revealed trnL-F had the highest identification rate (80%), followed by trnH-psbA (66%). The matK showed optimal species-level discrimination with 0.7% intra-generic divergence and achieved strong bootstrap support in phylogenetic analysis. The multi-locus approach combining trnL-F, trnH-psbA, and matK achieved 86% identification success rate. This study contributes 107 novel sequences and provides essential molecular tools for reliable species authentication, supports conservation of ethnomedicinal plant diversity in the Philippines, and establishes a foundation for quality control in traditional medicine practice and international trade.